The Relationship between Religious Tourism and International Christians Visitor's Perceptions: A case study of a Mount Nebo Holy Site in the Hashemite Kingdom of Jordan - Al-Zoubi, Mohammad Ibrahim; Ibrahim, Yahaya (International Review of Management and Marketing, 2020)
Throughout the world, the tourism industry is developing at an astonishing rate and contributing to the economy. Since the past decade, it has been continuously evolving by diversifying itself. Within the tourism sector, religious tourism is considered a vital aspect where tourists are motivated due to religious aspects. Considering this aspect, Jordan must be analyzed for its business activities since religious tourism contributes significantly to the economy. Within the current research, the association amongst religious tourism and the perception of the Christian visitor towards the Holy Site of Mount Nebo would be analyzed. The empirical research would be carried out using the Likert Scales which is part of the survey method. The data gathered would be helpful in extracting information regarding the association of religious tourism at the Holy Site of Mount Nebo and the perception of Christian visitors. The dimensions used to measure the perception of the visitors are accessibility; security and safety; hospitality and local people; social life at the holy site area and; prices. According to the results, the perception of Christian visitors towards the five dimensions was significant. Within a statistical sense, these dimensions and religious tourism maintain a positive relationship. Keywords: Jordan, Religious tourism, Mount Nebo, Visitor's Perception, Holy Land, Christians tourists JEL Classifications: Z32, Z31, Z33, Z39, N95, Z12 DOI: https://doi.org/10.32479/irmm.9321